Evaluation of Waste Management Policy Formulation: Case Study of Implementation of Tomohon Mayor Regulation Number 30 of 2019 - Nofellina S.U. Rumajar; Michael Mamentu; Maxi M. Egeten; Novie R. Pioh; Burhan Niode (Newinera Publisher, 2024)
Waste is one of the many urgent problems to be resolved by local governments. Various regulations have been established. However, in its implementation it is faced with various obstacles. Failure in a policy is not only seen from the implementation aspect. However, it can also be studied from the formulation aspect. Researchers examined the Waste Management Policy Formulation by the Tomohon City Government. With the focus of the study on the policy formulation process, examine and analyze why the presence of Tomohon Mayor Regulation Number 30 of 2019 has not succeeded in overcoming the problem of waste accumulation and management at the Tomohon City Waste Final Processing Site located in Taratara Village. The research design used is qualitative. The research findings were that the problem analysis stage did not work because the preparation of Jakstrada only followed directions from the center through the pocket book for the preparation of Jakstrada which is a derivative of Jakstranas without any research or problem identification process. The development of measures process which is lacking in deepening the problem results in not maximizing the measurement of situations or conditions to formulate appropriate policies. The determination of impacts process was not carried out to estimate the level of success of the policies made. Budgeting problems were discovered which resulted in the policies that had been set not being able to run according to what was set and required in the waste management process.